An Artificial Intelligence Approach for Online Energy Optimization of Flexible Manufacturing Systems - Bakakeu Ngassam, Romuald Jupiter; Bauer, Jochen; Tolksdorf, Schirin; Klos, Hans-Henning; Peschke, Jörn; Fehrle, Adrian; Eberlein, Werner; Bürner, Johannes; Brossog, Matthias; Jahn, Lars; Franke, Jörg (Energy Efficiency in Strategy of Sustainable Production IV, 2018)

Development of an intelligent networking of storage heaters as decentralized energy storage for the power supplier - Bürner, Johannes; Braun, Thomas (Tagungsband zum 2. Green Factory Bavaria Kolloquium 2015, 2015)
Keywords: E|Home; Energie; Lastverschiebung

Die intelligente Wohnung als Baustein im Internet der Dinge: Potenzialanalyse und Konzept einer domänenübergreifenden Lösung - Bauer, Jochen; Kettschau, Anna-Katharina; Michl, Markus; Bürner, Johannes; Franke, Jörg (Erste Transdisziplinäre Konferenz zum Thema Technische Unterstützungssysteme, die die Menschen wirklich wollen, 2014)
Keywords: AAL; E|Home; Energie; Smart Home

Elektrische Speicherheizungen als Instrument zur elektrischen Lastverschiebung - Bürner, Johannes; Franke, Jörg (HLH, Heizung Lueftung/Klima Haustechnik, 2016)
Keywords: DSM; Speicherheizung; E|Home

Energieeffiziente Raumbelüftung mit Wärmerückgewinnung unter Verwendung eines neuartigen Wirkprinzips - Praß, Julian; Bürner, Johannes; Franke, Jörg (Umwelt-Technologie und Energie in Bayern, 2018)

Energy-efficient room ventilation with heat recovery using a novel concept - Praß, Julian; Bürner, Johannes; Franke, Jörg (Environment and Energy in Bavaria, 2018)

Feldlabor der Energiewende - SWW Wunsiedel GmbH und E|Home-Center arbeiten Hand in Hand an der Umsetzung des Wunsiedler Wegs Energie 2.0 - Bürner, Johannes; Böhm, Ralf (Umwelt-Technologie und Energie in Bayern, 2015)

Heizsystem zur Schaffung eines angenehmen und belastungsarmen Raumklimas in Altbauten - Hein, Moritz; Stöber, Ralf; Fischerauer, Gerhard; Bauer, Jochen; Bürner, Johannes; Kettschau, Anna-Katharina; Franke, Jörg; Feller, Martin (Zukunft Lebensräume - Gesundheit, Selbstständigkeit und Komfort im demografischen Wandel Konzepte und Technologien für die Wohnungs-, Immobilien-, Gesundheits- und Pflegewirtschaft, 2016)

Identification of demand side management potentials within the sector of domestic living - Bürner, Johannes; Praß, Julian; Franke, Jörg (Environment and Energy in Bavaria, 2018)

Identifikation von Lastmanagementpotenzialen im Umfeld des privaten Wohnens - Bürner, Johannes; Praß, Julian; Franke, Jörg (Umwelt-Technologie und Energie in Bayern, 2018)

Innovative Flexible Heating System by the Use of Additive Plasma Coating Technology: Heating Where Heat Is Needed by Additive Metallization of Furniture and Walls - Braun, Thomas; Bürner, Johannes; Michl, Markus; Schaller, Lukas; Böhm, Ralf; Franke, Jörg (Proceedings of the 4th International Conference on Smart Energy Grid Engineering (SEGE), 2016)

Intelligente Wohnung - Bauer, Jochen; Kettschau, Anna-Katharina; Michl, Markus; Bürner, Johannes; Franke, Jörg (Technische Unterstützungssysteme, 2015)

Model of a Power-to-Gas System with Fuel Cell in a Mixed Integer Linear Program for the Energy Supply of Residential and Commercial Buildings - Ebell, Niklas; Bott, Andre; Beck, Tobias; Bürner, Johannes; Praß, Julian; Franke, Jörg (Applied Mechanics and Materials, 2017)
In the field of energy supply for residential and commercial buildings, the optimal operation, system configuration and sizing of generation as well as storage technologies are essential steps for cost-efficient investments. In current research, flexibility options for electricity from growing renewable energies attract attention. One of the considered options is the power-to-gas technology in combination with fuel cells. Linear Programs for optimal system operation exist for example for distributed energy systems. In this study we propose a Mixed Integer Linear Program of a power-to-gas unit consisting of an electrolyzer, a fuel cell and a hydrogen storage. For the fuel cell a minimum load and a non-linear efficiency curve is taken into account. The non-linear efficiency curve is approximated by piecewise linearization. Bilinear products in the modeling of the efficiency curve are being substituted to maintain full power plant sizing and operation functionality. Different fuels, such as natural gas and hydrogen to be converted in the fuel cell, are implemented as well. As a result, we show that a detailed model of the non-linear efficiency curve of a fuel cell leads to more accurate results concerning the system operation. The configuration of system components in the observed energy system changes. Especially the battery system experiences a change in sizing and operation. However, solving time of the model is increasing dramatically. Our results demonstrate a valuable approach to compare the results of a Linear Program to a Mixed Integer Linear Program. Hence giving the possibility to evaluate the necessity of detailed over simplified models regarding calculation of cost-effectivenes
Keywords: power-to-gas; Mixed Integer Linear Program; optimal operation; system configuration; fuel cell; load-dependent efficiency

Neue Ansätze für Energiemanagement und Energieeffizienz in der Produktion - Böhm, Ralf; Praß, Julian; Bürner, Johannes; Franke, Jörg (Umwelt-Technologie und Energie in Bayern, 2018)

Plasma-assisted additive apply of electric conductive structures for heating applications in the home environment - Braun, Thomas; Bürner, Johannes (Tagungsband zum 2. Green Factory Bavaria Kolloquium 2015, 2015)
Keywords: additiver Auftrag; E|Home; Leiterbahn

Potential Analysis of the Use of Electric Storage Heaters for Demand Side Management Applications - Bürner, Johannes; Braun, Thomas; Gaus, Michael; Michl, Markus; Franke, Jörg (Proceedings of the 4th International Conference on Smart Energy Grid Engineering (SEGE), 2016)

Sensor solutions for an energy-efficient and user-centered heating system - Hein, Moritz; Stöber, Ralf; Meiler, Michael; Schaller, Daniel; Zehle, Rebecca; Fischerauer, Gerhard; Bauer, Jochen; Bürner, Johannes; Franke, Jörg; Becher, Thomas; Feller, Martin; Maul, Joachim (Journal of Sensors and Sensor Systems, 2017)

SmartEco - An Approach Using Electric Storage Heaters for Demand Side Management - Bürner, Johannes; Kleineidam, Gerhard; Braun, Thomas; Skibbe, Alexander; Franke, Jörg (Advanced Engineering Forum, 2016)

SmartEco: An Integrated Solution from Load Balancing between the Grid and Consumers to Local Energy Efficiency - Bürner, Johannes; Ditter, Alexander; Fey, Dietmar; Franke, Jörg (IEEE/ACM 8th International Conference on Utility and Cloud Computing (UCC), 2015)

SmartEco - Ein Ansatz zur Nutzung elektrischer Wärmespeicher zum Demand Side Management - Bürner, Johannes; Franke, Jörg (Tagungsband zum 1. E|Home-Symposium 2016, 2016)

Smart Energy and Grid: Novel Approaches for the Efficient Generation, Storage, and Usage of Energy in the Smart Home and the Smart Grid Linkup: Foundations, Principles, and Applications - Praß, Julian; Weber, Johannes; Staub, Sebastian; Bürner, Johannes; Böhm, Ralf; Braun, Thomas; Hein, Moritz; Michl, Markus; Beck, Michael; Franke, Jörg (Smart Cities: Foundations, Principles, and Applications, 2017)

Smart Factory Meets Smart Grid: Cyber-Physical Compressed Air Systems Enable Demand Side Management in Industrial Environments - Böhm, Ralf; Bürner, Johannes; Franke, Jörg (Energy Efficiency in Strategy of Sustainable Production, 2015)
In electric energy systems based on renewable generation plants supply and demand often do not occur in the same period of time. Consequently demand side management is gaining importance whereby decentralized automation offers opportunities in industrial environments. Compressed air systems on industrial plants consist of air compressors, compressed air reservoirs and compressed air lines. With suitable dimensioning those industrial compressed-air systems can be used for demand side management purpose. As power consumption of industrial air compressors ranges between a few and several hundred kilowatts each, swarms of communicatively connected air compressors can contribute to the stabilization of power grids. To avoid costly production downtime it is to ensure, that a reliable, non-disruptive supply of compressed air can be maintained at all time. Industrial compressed air systems equipped with automation technology and artificial intelligence, which hereinafter are referred to as Cyber-Physical Compressed Air Systems (CPCAS), allow new business models for utilities, industrial enterprises, compressor manufacturers and service providers. In addition to basic operating parameters like current air pressure and status, those systems can process further information and create, for example, profiles on compressed air consumption over time. By enriching those profiles with data on pressure, volumes, system restrictions and current production requirements (plans), the CPCAS can identify the available potential for demand side management. Ipso facto predictive power on electricity consumption is increasing. By providing the information obtained to the power company or a service provider, savings in electricity costs may be achieved. Expenses within the industrial company may be lowered further as compliance with agreed load limits is being improved by automatic shutdown of air compressors upon reaching the load limit. Within this article the structure of the aforementioned Cyber-Physical Compressed Air Systems is presented in more detail, relations between the major actors are being shown and possible business models are being introduced.
Keywords: Cyber-Physical Systems; Demand Side Management; Energy Efficiency; Industrial Compressed-Air Systems

Smart Heating System for Old Buildings - An Approach to the Decentralized Use of Renewable Energies - Hein, Moritz; Stöber, Ralf; Fischerauer, Gerhard; Bürner, Johannes; Franke, Jörg; Feller, Martin; Maul, Joachim (Advanced Engineering Forum, 2016)

SMARTLOCATE – INDOOR LOCALIZATION WITH BLUETOOTH BEACONS AND SMARTPHONE SENSORS - Bauer, Jochen; Bakakeu Ngassam, Romuald Jupiter; Hopfengärtner, Michael; Bürner, Johannes; Braun, Thomas; Schäfer, Franziska; Wittmann, Maximilian; Fehrle, Adrian; Maußner, Benedikt; Lechler, Tobias; Meiners, Moritz; Konrad, Christoph; et al. (Smart Public Building 2018 Proceedings, 2018)